An evaluation of textual prompts and generalized textual instruction‐following. Issue 4 (23rd October 2019) - Phillips, Cara L.; Vollmer, Timothy R.; Porter, Allen
Abstract : The benefit of permanent prompts depends on the extent to which their use is generalized. Previous research has demonstrated both control by and efficacy of pictorial prompts (e.g., Phillips & Vollmer, 2012). The present studies similarly evaluated stimulus control by textual prompts. Six school aged children with intellectual disabilities were taught to complete four 5‐step instructional sets under the control of textual prompts. All 6 subjects showed some generalization to the final set. The results suggest that training served 1 of 3 purposes: (a) established control by the textual prompts or the ordinal sequence thereof, (b) addressed a reading deficit, or (c) addressed the lack of a motivating operation during baseline. Training a single task sequence may not be sufficient for acquisition of generalized textual instruction‐following. However, establishing appropriate stimulus control by the textual prompts may facilitate acquisition of a generalized repertoire.